Optimizing Village Funds Through BUMDes Managerial Model in the Local Trade Sector - Rahmaini, Putri (Journal of Government Insight, 2025)
The management of Village Funds through Village-Owned Enterprises (BUMDes) in the local trade sector offers great opportunities while posing complex institutional challenges. This article aims to examine how managerial models within BUMDes can effectively optimize Village Funds using a reflective approach grounded in institutional theory. This research adopts a qualitative-descriptive method through a literature review of eight academic books and seven scholarly journals. The findings indicate that the success of local trade business management by BUMDes depends not merely on capital support but primarily on the existence of institutional structures that regulate roles, incentives, and sanctions with clarity. When village institutions are capable of establishing rational and consistent rules of engagement, Village Funds can transform into productive and sustainable capital. This article recommends the formation of adaptive, transparent, and enterprise-oriented institutional systems within all BUMDes trade units.